A Trifluoroacetic Acid Catalyzed Domino Reaction as an Approach to Amino Acid Derived 2,3-Dihydro-1H-1,5-benzodiazepines - Bera, Saurav; Kandiyal, Pancham S.; Ampapathi, Ravi S.; Panda, Gautam (Synlett, 2014)
Trifluoroacetic acid catalyzed condensation of aromatic amines with substituted benzaldehydes followed by intramolecular cyclization furnishes a highly effective synthesis of amino acid derived 2,3-dihydro-1H-1,5-benzodiazepines. The strategy provides an efficient access to a library of benzodiazepines that can be explored for potential pharmaceutical or biological activities.
Keywords: amino acids; heterocycles; benzodiazepine; domino reaction; intramolecular cyclization